Where did the finch go? Insights from radio telemetry of the medium ground finch (Geospiza fortis). Issue 4 (26th April 2022) - Beausoleil, Marc‐Olivier; Camacho, Carlos; Rabadán‐González, Julio; Lalla, Kristen; Richard, Roxanne; Carrion‐Avilés, Paola; Hendry, Andrew P.; Barrett, Rowan D. H.
Abstract: Movement patterns and habitat selection of animals have important implications for ecology and evolution. Darwin's finches are a classic model system for ecological and evolutionary studies, yet their spatial ecology remains poorly studied. We tagged and radio‐tracked five (three females, two males) medium ground finches ( Geospiza fortis ) to examine the feasibility of telemetry for understanding their movement and habitat use. Based on 143 locations collected during a 3‐week period, we analyzed for the first time home‐range size and habitat selection patterns of finches at El Garrapatero, an arid coastal ecosystem on Santa Cruz Island (Galápagos). The average 95% home range and 50% core area for G .  fortis in the breeding season was 20.54 ha ± 4.04 ha SE and 4.03 ha ± 1.11 ha SE, respectively. For most of the finches, their home range covered a diverse set of habitats. Three finches positively selected the dry‐forest habitat, while the other habitats seemed to be either negatively selected or simply neglected by the finches. In addition, we noted a communal roosting behavior in an area close to the ocean, where the vegetation is greener and denser than the more inland dry‐forest vegetation. We show that telemetry on Darwin's finches provides valuable data to understand the movement ecology of the species. Based on our results, we propose a series of questions about the ecology and evolution of Darwin's finches that can be addressed using telemetry. Abstract : Movement patterns and habitat selection of animals have important implications for ecology and evolution. Darwin's finches are a classic model system for ecological and evolutionary studies, yet their spatial ecology remains poorly studied due to concerns about the use of telemetry. In this paper, we test the feasibility of radio‐tracking medium ground finches and demonstrate its utility by characterizing for the first time the habitat selection patterns of breeding ground finches in the arid coastal zone of Santa Cruz Island (Galápagos).